2015
DOI: 10.1039/c4fo01164c
|View full text |Cite
|
Sign up to set email alerts
|

Naringin protects against anoxia/reoxygenation-induced apoptosis in H9c2 cells via the Nrf2 signaling pathway

Abstract: Naringin (Nar) is a major and active flavanone glycoside derivative of several citrus species. The antioxidant properties of Nar have an important function in its cardioprotective effects in various models. However, the effects of Nar on Nrf2 activation and the expression of its downstream genes in myocardial cells are yet to be elucidated. This study was designed to investigate the protective effects of Nar against anoxia/reoxygenation (A/R)-induced injury in H9c2 cells and determine its effects on the activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 47 publications
5
25
0
Order By: Relevance
“…Also, NIN gets converted to naringenin, which has been shown to impart health‐promoting properties like including anti‐inflammatory and antioxidant activities . A number of reports advocate the ability of NIN to exert its antioxidant and cytoprotective property via activating Nrf2, which aids in the activation of various antioxidants such as GSH, Glutathione S‐transferase (GST) and downstream molecules that help in ameliorating against oxidative stress . Hence, we put forward that plant‐derived polyphenolic compounds will help in reducing the adverse effects of cadmium‐mediated hepatotoxicity.…”
Section: Introductionsupporting
confidence: 87%
“…Also, NIN gets converted to naringenin, which has been shown to impart health‐promoting properties like including anti‐inflammatory and antioxidant activities . A number of reports advocate the ability of NIN to exert its antioxidant and cytoprotective property via activating Nrf2, which aids in the activation of various antioxidants such as GSH, Glutathione S‐transferase (GST) and downstream molecules that help in ameliorating against oxidative stress . Hence, we put forward that plant‐derived polyphenolic compounds will help in reducing the adverse effects of cadmium‐mediated hepatotoxicity.…”
Section: Introductionsupporting
confidence: 87%
“…MDA is recognized as an indirect oxidative stress marker of cellular injury due to itself is one of the end products of lipid peroxidation [29]. SOD and GSH-Px are known as main endogenous antioxidant enzymes which can neutralize free radicals and protect cells from ROS insults [30]. In our hands, we found that H9c2 cells exposed to H 2 O 2 showed a significant increase in MDA levels (Figure 4(a)), which was ameliorated by pretreatment with 5 and 10  μ M caffeate derivatives (BZC, CAPE, and CNC).…”
Section: Resultsmentioning
confidence: 99%
“…Its therapeutic potential has been reported d for various diseases including atherosclerosis, cardiovascular disorders, and cancers [ 15 ]. Previous studies have shown that naringin protects against LPS-induced endotoxin shock in mice and RAW264.7 macrophages [ 16 , 18 , 24 ], and upregulates HO-1 expression via phosphatidylinositol 3-kinase/Akt, ERK1/2, protein kinase C-α, and NF-E2-related factor-2 in H9C2 myoblast cells [ 25 ]. However, the precise mechanism underlying naringin’s anti-septic action in macrophages remained unclear.…”
Section: Discussionmentioning
confidence: 99%